Paete carving capital a study on the current economic status of the carving industry in Paete, Laguna - Biasbas, Karmen B. (2012)
Paete, a municipality in Laguna, is the Carving Capital of the Philippines and is the only artisan village that has the whole town as artists in Asia. Given the title and the centuries of age of the wood carving industry of Paete, it is a very good example of an old business that is left-behind in terms of technology. The lack of exploitation of technology, such as the internet, imprints a notion of non-competitiveness to the wood carving industry in Paete. This leaves the researcher a question whether Paete is still making money on the wood carving business. This also pushes the researcher to aim to determine the current market status of the Paete wood carving industry and the reason behind either its downfall or success. The Marketing Mix will be used as guide to the study as well as the SWOT analysis. These tools will help achieve the objectives of the study since these tools are especially for market research. The study came out with results that the income of the wood carving industry is fluctuating and is inclined to depreciate its value in the near future if the current marketing and advertising strategies, or lack thereof, is retained. The results showed that th e Poon and the Taka are the two strongest product categories at present because they are fast moving. On the other hand, the other products are almost just by another basis only. The current economic status of the wood carving industry in Paete is fluctuating because of the following: climate change, Global economic crisis, lack of knowledge on the current technologies in advertising, no ceiling price on products.
"April 2012."
Thesis (BFA)--University of the Philippines, Diliman.
Keywords: Wood-carving -- Philippines; Wood-carving -- Philippines -- Marketing